(3OjhGf GHf GdgGFes - (3GHf GdgGFe , TgGH GdOjf CHh GdYHGS GdefUhQj,J (B887 (3g` s
(3ChdgG (B:s
(3hHYO abO fXe GdfGS aCcKQhG, hWqhdhG ajg heG bUQhG HGfJ SYGO abdHj Gdjhe eHJhd heOeYj SGFd YfgG heSFhd s
(3BNQgG (B:s
(3acja hgPg GdCTjGA Mb CJJ Yf CaVd GdQSd GdUOhb s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B220s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B487 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B245 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B819s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdhWfjI HeOQjO (B(4962) s
Keywords: (3GdCOHs